Respostas

2013-06-03T18:45:33-03:00

vejamos;

 

b=9,2                                     b    +  c  =    16,1

                                               9,2+6,9 =     16,1

c= 16,1-b

c=16,1-9,2                              b   *  c   = 63,48                                             

                                                  9,2*6,9 =  63,48

 

c=6,9

 

Usando o teorema de pitágoras temos:

 

11,5² = (9,2)² + (6,9)²

132,25 = 84,64+47,61

132,25= 132,25

 

 

Concluimos que a hipotenusa é igua a 11,5cm

 

 

1 5 1